Utilisation of ceramic waste aggregate and its effect on Eco-friendly concrete: A review. (15th April 2022) - Magbool, Hassan M.
Abstract: The literature has emphasised the huge potential of using recycled waste ceramic aggregate (RWCA) as a substitute material for fine and coarse aggregates either as admixtures or reinforcements. The objective of this research is to provide a complete review of published studies on the use of RWCA in concrete and its effect on concrete characteristics, such as workability, mechanical properties and durability. Moreover, this research aims to examine the influence of RWCA on durability by analysing information regarding its microstructure obtained through scanning electron microscopy. The findings indicate that the use of RWCA as partial substitute reduces workability but improves compressive, flexural and durability properties. Recommendations and observations are provided for future research. Highlights: The physical and chemical properties of recycled ceramic is reviewed. The impact of recycled ceramic on fresh and hardened properties of green concrete is discussed. The effect of recycled ceramic on durability and microstructure properties of green concrete is reviewed. Relationships between concrete properties have been discussed. Recommendations and observations are advanced for future research.